2019
DOI: 10.1007/s42452-019-0812-x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dinitrotoluene from petrochemical wastewater by Fenton oxidation, kinetics and the optimum experiment conditions

Abstract: The performance of Fenton oxidation processes with simultaneous application of two oxidants including (H 2 O 2 ) and sodium persulfate (Na 2 S 2 O 8 ), in the presence of iron (Fe 2+ ) as a catalyst to oxide dinitrotoluene (DNT) was investigated. For optimization of processes, the effect of operational parameters such as solution pH, oxidant dosages, reaction time and initial DNT concentrations on their performance was evaluated. All experiments were conducted at room temperature (25 ± 2 °C). For all studied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Several research efforts were made in the Fenton oxidation processes. To remove dinitrotoluene (DNT) from petrochemical wastewater, the Fenton oxidation process was tested with both hydrogen peroxide and sodium persulfate with ferrous iron as a catalyst (Takdastan, Ravanbakhsh, Hazrati, & Safapour, 2019). The system was less efficient in acidic conditions, and the DNT mineralization rate was more than 86%.…”
Section: Petrochemical Wastewatermentioning
confidence: 99%
“…Several research efforts were made in the Fenton oxidation processes. To remove dinitrotoluene (DNT) from petrochemical wastewater, the Fenton oxidation process was tested with both hydrogen peroxide and sodium persulfate with ferrous iron as a catalyst (Takdastan, Ravanbakhsh, Hazrati, & Safapour, 2019). The system was less efficient in acidic conditions, and the DNT mineralization rate was more than 86%.…”
Section: Petrochemical Wastewatermentioning
confidence: 99%
“…28−30 It was found that Na 2 S 2 O 8 can react with OH • and enhance the oxidation of the solution in a weakly basic solution. 31 For ships, seawater with a pH of 7.6−8.4 32 could be considered as a natural alkaline solvent. However, it is not clear if seawater is suitable for the Na 2 S 2 O 8 system to oxidize and remove NO.…”
Section: Introductionmentioning
confidence: 99%
“…Among these oxidants, Na 2 S 2 O 8 has been widely used in the removal of organic toxic gases, treatment of organic contaminants in groundwater, and remediation of diesel-contaminated soil for its high stability, low cost, environmental friendliness, and good oxidation properties. In recent years, Na 2 S 2 O 8 has gradually entered the field of wet denitrification to oxidize NO. , Many improved methods on additives or complex solutions for Na 2 S 2 O 8 solutions have been reported, which were mainly explored to improve the effect on the removal of NO x . It was found that Na 2 S 2 O 8 can react with OH · and enhance the oxidation of the solution in a weakly basic solution . For ships, seawater with a pH of 7.6–8.4 could be considered as a natural alkaline solvent.…”
Section: Introductionmentioning
confidence: 99%